Comunicación entre los miembros del gobierno autónomo descentralizado de la Parroquia Isla de Bejucal - Cercado Rodríguez, Yuliana Del Rosario (2020)
The present case study was highlighted in the GADP Isla de Bejucal, where the labor communication between all those who make up the government institution is analyzed, due to inconveniences caused by the different political ideologies in the normal development of internal activities, for this reason the The objective of this work is to determine the causes of the lack of communication in the work environment of the GADP Isla de Bejucal, for this reason it needs to implement adequate and updated communication methods to achieve an efficient work environment that motivates employees to generate ideas, know working as a team, mastering the different scenarios that are presented to them, being predisposed to continuous improvement to achieve the common mission. The methodology constituted by the type of descriptive research, the inductive method was applied, together with the technique of survey, interview, (questionnaire) for data collection. The results obtained show that internal labor communication is inefficient, there is an affinity for political parties and they do not work as a team, they are only determined by their own interest